Peningkatan Hasil Belajar IPS Berbantuan Multy Platform Pada Siswa Kelas V SD - Florentina Winarti; Salamah Salamah (UM Purwokerto Press, 2022)
The purpose of this action research is to know the process of implementing multi-platform assisted learning to improve social studies learning outcomes for fifth-grade students at SDN Siraman III. The type of research used is Classroom Action Research. The time research was out from January 2021 to March 2021. The research location was at SDN Siraman III. The research subjects were 17 students of class V, consisting of L: 9 and P: 8. The object of the research was the result of social studies learning. The methodology used in this research is Classroom Action Research on improving social studies learning outcomes assisted by multi-platform. The steps of this Classroom Action Research include planning, action, observation, and reflection. The implementation consists of 2 cycles of measure. The obstacles in implementing this multi-platform assisted learning are signal difficulties and limited communication tools. Signal troublesome can get over by finding a place where the signal coverage is stronger. The limitations of communication tools in carrying out the task are apt a separate grace period. Multi-platform assisted learning with google meet, google classroom, and WhatsApp groups can accept by students. The proof is that response students are best, very enthusiastic in participating in online learning so that learning outcomes increase. This study concludes that multi-platform assisted learning can improve social studies learning outcomes for fifth graders at SDN Siraman III. It is proven by an increase in learning outcomes in cycle 1 with an average of 68.71%, best denomination, increased to 90.06% in cycle 2 with a very best denomination.